PREVENTION OF ATHEROSCLEROSIS WITH REFERENCE TO OBESITY AND INADEQUATE NUTRITION AS RISK FACTORS FOR CARDIOVASCULAR DISEASES - Pelicic, Damir (HEALTH CARE, 2022)
This paper will present information from relevant data sources related to the prevention of atherosclerosis with a focus on obesity and inadequate nutrition as a risk factor for CVD. The World Health Organization estimates that 17.9 million people die each year from cardiovascular diseases (CVDs), which is a third of the world's death toll. CVDs are not only the leading cause of death, but also of illness and disability, which indicates their great public health importance. Endothelial dysfunction is thought to be an early stage of atherosclerosis. Atherosclerosis also occurs in children under the age of 10, while the risk of atherosclerosis increases with age. There are over 300 factors associated with atherosclerosis and key complications, coronary heart disease and stroke. The most important of these are obesity, physical inactivity, hypertension, smoking, inadequate nutrition, abnormal lipids, heredity, metabolic syndrome, diabetes and psychosocial factors.
Keywords: atherosclerosis, cardiovascular diseases, obesity, diet, risk factors, prevention